Training Needs Analysis (TNA) for Nurses at Ilaga Regional Hospital, Puncak Regency, Central Papua - Suhendra, Erik; Oktamianti, Puput; Ayuningtyas, Dumilah (Jurnal Indonesia Sosial Sains, 2025)
Nurse training at Ilaga Regional Hospital aims to improve nurses' quality, but its implementation does not have a significant impact. This must be addressed immediately, because the failure of ineffective, inefficient and irrelevant training to the needs of nurses at Ilaga Regional Hospital can hinder efforts to improve the quality of service at Ilaga Regional Hospital. This study aims to identify training needs at Ilaga Regional Hospital, using quantitative methods of survey data from the Hennesy-Hick’s questionnaire (n = 29, purposive sampling), consisting of 25 questions (five categories). Qualitative methods use semi-structured interview data (n = 14) consisting of 42 questions (organizational analysis, task analysis, personal analysis). Training needs according to education level, agency of origin, age and length of service, namely administration and clinical skills. However, the competency gap is smaller in respondents S1 + Profession, the highest in IRNA, tends to decrease with age. and there is a variation in the gap in each category of length of service. The results of the organizational, task and personal analysis, there is a need for RME training, clinical skills, SOP training, and motivational training.